PENGARUH PROMOSI JABATAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA GURU PEGAWAI NEGERI SIPIL (STUDI PADA SMA NEGERI 6 KENDARI) - Muhamad Masri (Journal Publicuho, 2020)
The purpose of this study was to determine the effect of job promotion and work environment on the job satisfaction of Civil Servants (PNS) teachers in Kendari 6 High Schools (SMA), both simultaneously and partially. The sample in this study were all PNS teachers in SMA Negeri 6 Kendari, amounting to 57 people, the method of data collection using documentation and questionnaires. The measurement scale of the data used is the Likert scale and the data analysis method uses descriptive analysis method and multiple linear regression analysis. The results of this study indicate that simultaneous promotion of position and work environment has a positive and significant effect on job satisfaction of PNS teachers at SMA Negeri 6 Kendari. Likewise partially, the promotion of position and work environment has a positive and significant effect on job satisfaction of PNS teachers in SMA Negeri 6 Kendari.